Artificial Intelligence Technologies and the Performance of Nigerian Banks - Ademola Samuel Sajuyigbe; Sunday Festus Olasupo; Oloruntoba Oyedele; Adeniran Rahman Tella; Adebanji Williams Ayeni; Matthew Olubayo Omotoso (Universitas Airlangga, 2026)
Background: The Nigerian banking industry has encountered substantial challenges and opportunities arising from globalization, with AI emerging as a critical enabler of operational efficiency, customer service excellence, and improved financial performance. Objective: This study investigated the impact of AI technologies on the performance of Nigerian banks. Methods: The study drew data from 228 respondents across six selected banks through a structured questionnaire. Path Analysis-Structural Equation Modelling (PA-SEM) was employed for data analysis using STATA version 15. Results: The findings indicate that AI-driven applications—such as chatbots, personalized banking services, and automated loan processing—substantially enhance customer satisfaction and deposit mobilization. The results underscore the pivotal role of AI technologies in strengthening the performance of Nigerian banks amid globalization, positioning the sector for sustained growth and development. Conclusion: The findings highlight the transformative role of AI technologies in the global banking landscape, emphasizing their significance in enhancing efficiency, customer engagement, and overall sector growth. As AI advances, its strategic adoption will be essential for maintaining a competitive edge and supporting the future expansion of the Nigerian banking industry. Keywords: Chatbots, Personalized banking Services, Automated loan processing, AI JEL Classification: C45, E50, G21, J24